The current state of agrologistics in Ukraine and its impact on the state's agribusiness - Nycz-Wojtan, Sylwia (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The article examines the state of agrologistics in Ukraine in 2022 and its deterioration due to the ongoing war. The article aims to analyze the reasons for the increase in costs in agrologistics, structure the consequences of the agrologistics’ disruption, and justify their direct impact on the financial results of agricultural producers. The main methods of scientific research were chronological, systemic research, statistical, and structural analysis, which allowed exploring the modern cause-and-effect relationships between the state of agrologistics and the activities of agricultural sector enterprises in a logical sequence. The research resulted in proposals for overcoming the crisis in agrologistics and its further development. The conclusions emphasize the urgent need for investment in the modernization of transport infrastructure, as well as the necessity of improving coordination between agricultural producers and logistics service providers to ensure an efficient flow of exports. The authors conclude that this study provides valuable information on current challenges facing the agricultural sector in Ukraine and proposes solutions for its sustainable development.